Dominant Causes of Speaking Anxiety Among English Class Learners - Abid Azizy (ELITE JOURNAL, 2023)
This action research aims to explore the dominant causes of speaking anxiety among English Class learners, and to suggest effective strategies that can both help conquer learners’ fear of communication and boost their confidence level. English Class students suffer from a substantial level of communication apprehension. The findings of this study will be to the benefit of English Class learners as they can enhance learners’ oral communication skills which are impacted negatively by learners’ speaking anxiety. Keywords: Students’ Anxiety, Speaking, Dominant